Androgen receptor signaling regulates follicular growth and steroidogenesis in interaction with gonadotropins in the ovary during mini-puberty in mice - Devillers, Marie M.; François, Charlotte M.; Chester, Mélanie; Corre, Raphaël; Cluzet, Victoria; Giton, Frank; Cohen-Tannoudji, Joëlle; Guigon, Céline J. (Frontiers in Endocrinology, 2023)
In females, androgens contribute to ovarian diseases such as polycystic ovarian syndrome (PCOS), but their action is also crucial for ovarian physiology, i.e., follicular growth and estradiol (E2) synthesis during reproductive life, in interaction with the gonadotropins LH and FSH. However, it is unclear whether androgens already play a role in the ovary at mini-puberty, a phase of postnatal development with active follicular growth and high E2 levels. Therefore, we analyzed the potential actions of androgens on the ovary and their possible interaction with gonadotropins during this period in mice. We used molecular-based studies and pharmacological approaches in vivo and on cultured ovaries. We found that mini-pubertal ovaries produce significant amounts of testosterone and display androgen receptor (AR) expression in growing follicles, both under the control of LH. By blocking AR signaling either in vivo or in ovarian cultures, we found that this pathway may participate in the regulation of prepubertal E2 synthesis and follicular growth, possibly by regulating the expression of a number of key intra-ovarian regulators, including FSH receptor (Fshr), the aromatase enzyme converting androgens into estrogens (Cyp19a1) and the cell cycle inhibitor p27KIP1 (Cdkn1b). We further showed that AR may stimulate FSH-mediated regulation of Cyp19a1 through its action on Fshr mRNA abundance. Overall, this work supports the idea that AR signaling is already activated in mini-pubertal ovaries to regulate E2 synthesis and follicular growth, at the interplay with LH and FSH signaling. Its early action may, thus, contribute to the implementation of early ovarian function with possible impacts on reproductive function.